2021
DOI: 10.9734/jpri/2021/v33i28b31544
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of First Diagnosed Atrial Fibrillation in Patients Admitted with Acute Coronary Syndrome and with Impaired Renal Function with and without Diabetes Mellitus

Abstract: Objective: To determine the prevalence of first diagnosed atrial fibrillation in patients admitted with acute coronary syndrome and with impaired renal function with and without diabetes mellitus. Methodology: A total of 434 patients were selected from two different hospitals, 361 from NICVD, Tando Muhammad Khan and 73 from Isra University Hospital, Hyderabad. Both males and females, aged between 18 years to 70 years, first ever presented & admitted with acute coronary syndrome (ACS) and renal impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A further higher ratio of 5.6:1, and 4.7:1 of male/female were reported by the Studies done in south Punjab (Pakistan) and Saudi Arabia respectively. 11,12 23% of CAD patients were found to be diagnosed with DM in our work. A similar study done in China showed similar findings of 37% of CAD patients were diagnosed with DM during hospital stay.…”
Section: Discussionmentioning
confidence: 50%
“…A further higher ratio of 5.6:1, and 4.7:1 of male/female were reported by the Studies done in south Punjab (Pakistan) and Saudi Arabia respectively. 11,12 23% of CAD patients were found to be diagnosed with DM in our work. A similar study done in China showed similar findings of 37% of CAD patients were diagnosed with DM during hospital stay.…”
Section: Discussionmentioning
confidence: 50%